2017
DOI: 10.1080/00029157.2017.1316233
|View full text |Cite
|
Sign up to set email alerts
|

Staying the Course: Using Hypnosis to Help Cancer Patients Navigate Their Illness

Abstract: Although sometimes maligned and often misunderstood, clinical hypnosis can be utilized as a powerful adjunct for the treatment of mind-body conditions, including cancer. Unlike customary medical regimens that treat diseases of the body and psychotherapies that address disorders of the psyche, hypnosis is a uniquely customizable multi-tool that can augment the treatment of both physical and emotional disorders as well as their complex interactions. This article presents a longitudinal, phase-oriented, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…being so immersed in a pleasurably challenging task that time passes quickly) (Csikszentmihalyi & Csikzentmihaly, 1990 ), purpose in life (Ryff, 1989 , 2014 ), and successful aging (Carstensen, Fung, & Charles, 2003 ). Being impervious to negativity from others or due to life conditions is associated with better QOL outcomes (Abravanel & Sinha, 2015 ; Ginandes, 2017 ; McNulty, 2008 ; Ormel & Wohlfarth, 1991 ), and we believe constitutes an inner fortitude that enables mood stability. This inner fortitude may relate to recognizing a consistent and underlying core ‘self’ and maintaining a sense of integrity or constancy with oneself and one’s values.…”
Section: Main Text Introductionmentioning
confidence: 92%
“…being so immersed in a pleasurably challenging task that time passes quickly) (Csikszentmihalyi & Csikzentmihaly, 1990 ), purpose in life (Ryff, 1989 , 2014 ), and successful aging (Carstensen, Fung, & Charles, 2003 ). Being impervious to negativity from others or due to life conditions is associated with better QOL outcomes (Abravanel & Sinha, 2015 ; Ginandes, 2017 ; McNulty, 2008 ; Ormel & Wohlfarth, 1991 ), and we believe constitutes an inner fortitude that enables mood stability. This inner fortitude may relate to recognizing a consistent and underlying core ‘self’ and maintaining a sense of integrity or constancy with oneself and one’s values.…”
Section: Main Text Introductionmentioning
confidence: 92%
“… 105 With regard to hypnosis, a study of healing in cancer patients could be applicable to musculoskeletal pain; the results from a recent study concluded The intrinsic capacities of hypnotic phenomena, can be harnessed to effect perceptual and functional changes to offer symptom relief, re-establishment of systemic homeostasis, amelioration of cellular chemistry, and the acceleration of tissue healing. 106 …”
Section: Integrative Medicine Within the Self-healing Conceptmentioning
confidence: 99%
“…The intrinsic capacities of hypnotic phenomena, can be harnessed to effect perceptual and functional changes to offer symptom relief, re-establishment of systemic homeostasis, amelioration of cellular chemistry, and the acceleration of tissue healing. 106 …”
Section: Integrative Medicine Within the Self-healing Conceptmentioning
confidence: 99%
“…Medical hypnosis started being used more commonly in hospital psychiatry in the 1970s. It encompasses many techniques that can be adapted to individual needs and hospital situations as an adjunctive treatment of somatic, psychological, and psychosomatic disorders ( Häuser et al, 2016 ; Ginandes, 2017 ). Virtually all techniques use suggestions to positively influence emotions, cognitions, body sensations (pain, compression, etc.…”
Section: Introduction: Medical Hypnosis In Heart Surgerymentioning
confidence: 99%